Dinamika Proses Mutasi Jabatan Pada Pemerintahan Kabupaten Pidie Periode 2017-2022 - Muhammad Ichwan; Effendi Hasan (Jurnal Ilmiah Mahasiswa Fakultas Ilmu Sosial & Ilmu Politik, 2022)
ABSTRAKProses mutasi yang di lakukan oleh pemerintah Kabupaten Pidie memiliki banyak permasalahan. Hal ini terlihat dari tidak adanya proses uji kelayakan dan penempatan posisi beberapa pejabat eselon II dan III yang cenderung terlihat kontroversial yang bersifat menimbulkan (perdebatan, pertentangan, atau persengketaan) yang berkepanjangan dalam suatu masyarakat, penempatan pejabat tidak sesuai dengan lokasi kerja, serta sistem jual beli jabatan (yang mampu memberikan setoran lebih tinggi bisa menduduki jabatan yang strategis). Penelitian ini bertujuan untuk Untuk mengetahui dan menjelaskan proses mutasi jabatan terhadap pejabat eselon II dan III di era Bupati Roni Ahmad pada Kabupaten Pidie dan Untuk mengetahui peran dan wewenang Bupati Roni Ahmad dalam proses mekanisme mutasi jabatan. Adapun jenis penelitiannya adalah Kualitatif, Teknik Pengumpulan data pada pengambilan data primer menggunakan wawancara dan observasi langsung dengan informan, sedangkan pemerolehan data skunder menggunakan dokumentasi. Hasil Penelitian menunjukkan Bupati memiliki peran dan wewenang yang sangat penting dalam proses mutasi jabatan. Hal ini dapat dilihat dari bupati memiliki hak khusus dalam menentukan pejabat yang akan dilantik. Semua bentuk permasalahan yang terjadi dalam proses mutasi yang dilakukan oleh pemerintah kabupaten Pidie tidak terlepas dari hak yang dimiliki oleh bupati itu sendiri. Berdasarkan hasil penelitian tersebut dapat disimpulkan bahwa Bupati di Kabupaten Pidie melakukan mutasi jabatan belum sepenuhnya berorientasi pada aturan yang berlaku. Hal ini dapat dilihat dari tahapan pengumuman seleksi, tahap seleksi berkas, tahap mengikuti ujian, tahap penentuan tiga besar dan tahap panggilan oleh bupati masih didominasi oleh sisi politiknya dan masih mempertimbangkan hubungan kedekatan sehingga keahlian dan ketrampilan bukanlah dasar penilaian yang utama. Dyinamics Of Position Mutation Process In Pidie District Government Period 2017-2022 ABSTRACTThe mutation process carried out by the Pidie Regency government has many problems. This can be seen from the absence of a due diligence process and the placement of positions of several echelon II and III officials which tend to look controversial and causes prolonged (debates, conflicts, or disputes) in a society, the placement of officials is not in accordance with the work location, as well as the selling system. Buy positions (who are able to provide higher deposits can occupy strategic positions). This study aims to find out and explain the process of a job transfer for echelon II and III officials in the era of Regent Roni Ahmad in Pidie Regency and to find out the role and authority of Regent Roni Ahmad in the process of the job transfer mechanism. The Merit System is a very appropriate and adequate system for the development of bureaucratic Human Resources because it provides an overview of bureaucratic arrangements in a professional and proportional manner (Tamim 2005, p. 86). The non-use of the merit system as a basis for assessment in the selection of officials can lead to the low professionalism of government officials in carrying out their work and functions. The type of research is qualitative, data collection techniques in primary data collection using interviews and direct observation with informants, while secondary data collection uses documentation. The results of the study show that the Regent has a very important role and authority in the process of job transfer. This can be seen from the regent has special rights in determining the officials to be inaugurated. All forms of problems that occur in the mutation process carried out by the Pidie district government cannot be separated from the rights of the regent himself. Based on the results of this study, it can be concluded that the Regent in Pidie Regency has not been fully oriented to the applicable regulations. This can be seen from the selection announcement stage, file selection stage, examination stage, the stage of determining the top three and the call stage by the regent which is still dominated by the political side and still considers the close relationship so that expertise and skills are not the basis for a good assessmen.